Will Taming Generative AI Through Regulations Suffocate Productivity and Innovation? - Kumar, Rohit (Global journal of Business and Integral Security, 2023)
ChatGPT is a form of generative AI, considered to be part of Artificial General Intelligence (AGI). Generative AI is widely recognized to have huge potential for productivity gain and accelerating innovation across industries, sectors and business processes. AI regulations in different countries are primarily targeted for Artificial Narrow Intelligence (ANI) solutions. A rush to regulate generative AI can hamper the potential productivity and innovation gain whereas, lack of proper regulations can adversely affect individuals, companies, and society.